PEOPLE, ORGANIZATIONS AND MATERIALS FOR ETS MESSAGE (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Susan Stuntz to Peter Sparber regarding indoor air quality. Discusses people, organizations, and marketing strategies involved in dealing with secondhand smoke issues. Calls for a media campaign and use of labor unions.